Evaluation of Serum Levels of Transient Receptor Potential Cation Channel Subfamily V Member 1, Vasoactive Intestinal Polypeptide, and Pituitary Adenylate Cyclase-Activating Polypeptide in Chronic and Episodic Migraine: The Possible Role in Migraine Transformation - Togha, Mansoureh; Ghorbani, Zeinab; Ramazi, Samira; Zavvari, Fahime; Karimzadeh, Fariba (Frontiers in Neurology, 2021)
Objectives: This study aimed to investigate the role of serum levels of transient receptor potential cation channel subfamily v member 1 (TRPV1), vasoactive intestinal peptide (VIP), and Pituitary adenylate-cyclase-activating polypeptide (PACAP) in the development and also the transformation of migraine in patients suffering from migraine. Methods: Eighty-nine participants with a mean age of 39 years were divided into 23 episodic migraine (EM), 36 chronic migraine (CM), and 30 healthy control groups. Demographic, anthropometric, and headache characteristics information, as well as blood samples, were collected. Serum levels of TRPV1, VIP, and PACAP were measured using the enzyme-linked immunosorbent assay technique. Results: Based on our findings, the serum level of TRPV1 was significantly higher in CM compared to the control group (P<0.05), whereas serum levels of VIP (P<0.01) and PACAP (P<0.05) in the EM group was significantly more than the control group. There was no significant difference between EM and CM groups. Conclusions: An elevation in the serum levels of TRVP1 among chronic migraineurs and increments in the levels of VIP and PACAP were observed among episodic migraine patients compared to healthy subjects. However, our data failed to demonstrate the probable role of these biomarkers in migraine progression, and more studies are needed to clarify the molecular mechanisms involved in migraine progression.